2014
DOI: 10.1111/rda.12294
|View full text |Cite|
|
Sign up to set email alerts
|

Immunolocalization of the Cholesterol Transporters ABCA1 and ABCG1 in Canine Reproductive Tract Tissues and Spermatozoa

Abstract: The mammalian sperm membrane undergoes cholesterol efflux during maturation and fertilization. Although ATP-binding cassette (ABC) transporters are known to transport cholesterol through cell membranes in other organs, their presence in canine testis, epididymis and sperm has not been proven to date. Hence, the aim of the present study was to localize the ABC transporters ABCA1 and ABCG1 in canine testicular and epididymidal tissue as well as in spermatozoa membranes. To this end, semen samples from 12 dogs as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Cholesterol efflux in sperm has been shown to be dependent upon active externalization of the sterol to make it available to sterol acceptors in the medium; this takes place through members of the ATP-binding cassette (ABC) transporter superfamily in mice (Morales et al 2012). ABCA1, ABCA7, ABCA17, and ABCG1 have been detected in mouse sperm (Morales et al 2008) and ABCA1 has also been identified in dog sperm (Palme et al 2014). Inhibition of ABCA1, ABCA7, and ABCG1 in mouse sperm in turn inhibits IVF, confirming that cholesterol efflux plays a core role in the physiology of capacitation and gamete interaction.…”
Section: Introductionmentioning
confidence: 69%
“…Cholesterol efflux in sperm has been shown to be dependent upon active externalization of the sterol to make it available to sterol acceptors in the medium; this takes place through members of the ATP-binding cassette (ABC) transporter superfamily in mice (Morales et al 2012). ABCA1, ABCA7, ABCA17, and ABCG1 have been detected in mouse sperm (Morales et al 2008) and ABCA1 has also been identified in dog sperm (Palme et al 2014). Inhibition of ABCA1, ABCA7, and ABCG1 in mouse sperm in turn inhibits IVF, confirming that cholesterol efflux plays a core role in the physiology of capacitation and gamete interaction.…”
Section: Introductionmentioning
confidence: 69%
“…OCTN2 has also been characterized for its ability to transport carnitine, an important nutrient for male fertility, in MGT tissues [51]. Several ABC transporters have also been implicated in cholesterol transport within the testis, spermatozoa, and epididymis [5255]. …”
Section: Discussionmentioning
confidence: 99%
“…ABC transporters are a protein superfamily characterized by the presence of ATP-binding cassette (ABC) domains that are involved in inward and outward transport of a wide variety of substrates such as metabolites, drugs, and lipids. In particular, our analysis demonstrates that the ABC transporters play a key role in epididymal biochemistry of sperm membrane rearrangement [Ouvrier et al 2009;Jones and Cry 2011;Morales et al 2012;Caballero et al 2012;Gregory and Cyr 2014;Palme et al 2014]. They are a superfamily of more than 250 transmembrane proteins characterized by a region that spans about 180 amino acids and contains three highly conserved motifs: the Walker A/P-loop (12 amino acids), a signature motif/ C-loop (5 amino acids), and the Walker B motif (5 amino acids) [George and Jones 2012].…”
Section: Node Degreementioning
confidence: 65%